2004
DOI: 10.2165/00007256-200434110-00001
|View full text |Cite
|
Sign up to set email alerts
|

Non-Intentional Doping in Sports

Abstract: Compulsory drug testing was introduced in 1968 by the International Olympic Committee. Since then, several doping cases have been reported in sports competition world wide. Positive results are based on the detection of prohibited substances, their metabolites and markers in biological (mainly urine) samples supplied by athletes. In some cases, the evidences were not contested and athletes admitted the use of banned substances. However, in other cases, athletes denied the use of doping to enhance performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
0
22
0
4
Order By: Relevance
“…In subsequent years, more and more studies were published that confirmed the hypothesis that supplements could indeed cause unintentional doping infractions 1622. Other publications showed that unlabelled doping substances can be found in a variety of products2326 and thoroughly discussed the risks for elite athletes 2730…”
Section: The Doping Risk Of Supplementsmentioning
confidence: 96%
“…In subsequent years, more and more studies were published that confirmed the hypothesis that supplements could indeed cause unintentional doping infractions 1622. Other publications showed that unlabelled doping substances can be found in a variety of products2326 and thoroughly discussed the risks for elite athletes 2730…”
Section: The Doping Risk Of Supplementsmentioning
confidence: 96%
“…A substantial number of medications, nutritional supplements, beverages and herbal products containing doping substances (reviewed by Yonamine et al 3) can be obtained from the internet, drug store or supermarket, without prescription. These products present a serious risk for athletes.…”
Section: Why Preventing Unintentional Doping Is Important?mentioning
confidence: 99%
“…However athletes may dope unintentionally because they are not aware that food, drinks, supplements, or medications may contain doping substances 2 3. Therefore, one of the key antidoping strategies of WADA, apart from doping control, is to enhance athletes’ antidoping awareness and their capacity to avoid unintentional doping.…”
mentioning
confidence: 99%
“…Another issue of concern is the increasing number of "non-intentional" doping cases in sports [13,14]. Pluim [5] reported that 67.5% of doping cases in tennis at independent hearings accepted that there was no intent to enhance performance.…”
Section: Discussionmentioning
confidence: 99%